Direct And Indirect Spatial Effects Of Spatial Panel Data Models For Trade Of Comesa - Hamzalouh, Lubna M Omar (2018)
The accuracy of geospatial information enables to study the spatial effects of economic variables on the trading activities countries of Common Market for Eastern and Southern Africa (COMESA). Hence, this thesis describes the spatial panel models for the analysing the trading activities of COMESA countries. The selection between spatial random or fixed effects models is determined by Hausman Test. In this thesis, it found strong evidence that there is a spatial dependence on the export and import of COMESA. Spatial dependence is a case where results in a given country seem to depend on results or other the factors from another country. Results showed that the Spatial Durbin Model with fixed time effect specification should be considered and tested in most of the states in this thesis. Furthermore, the indirect and direct effects among COMESA countries were estimated, and the role of direct and indirect effects in measuring imports and exports were empirically explained. Concerning research significance and originality, and to the best of researcher’s knowledge, this is the first thesis that delivers a comprehensive picture of COMESA regional trade. This study also contributes to the theory by providing a methodological flowchart to help new researchers save their time by using clear steps to analysis of spatial panel models and choosing the best spatial model. All explanatory variables for intra-country imports are statistically significant that include GDP, population, GGFCE, import costs and exchange rate ( 0.377, -0.206, 0.448, 0.648 and 0.079 respectively). Moreover, the GDP for intra-countries exports and the cost to export are statistically significant (0.927, -0.722) respectively.